2019
DOI: 10.1053/j.gastro.2019.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic Primary Afferent Neurons Link Visceral Pain to Colon Motility Through a Spinal Reflex in Mice

Abstract: Author names in bold designate shared co-first authorship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 51 publications
4
44
0
1
Order By: Relevance
“…However, when it comes to EA, the influence factors will be complicated by electrical stimulation. It is reported that simple focal electrical stimulation on mouse colon, even without acupuncture needle insertion, could produce phased-locked calcium signals in myenteric neurons and produced colon contractions to improve gastrointestinal function [84]. Also, Rafael et al demonstrated EA at the sciatic nerve controls systemic inflammation by inducing a vagal activation of dopamine decarboxylase, while EA with a wood toothpick did not inhibit cytokine levels [21].…”
Section: 1mentioning
confidence: 99%
“…However, when it comes to EA, the influence factors will be complicated by electrical stimulation. It is reported that simple focal electrical stimulation on mouse colon, even without acupuncture needle insertion, could produce phased-locked calcium signals in myenteric neurons and produced colon contractions to improve gastrointestinal function [84]. Also, Rafael et al demonstrated EA at the sciatic nerve controls systemic inflammation by inducing a vagal activation of dopamine decarboxylase, while EA with a wood toothpick did not inhibit cytokine levels [21].…”
Section: 1mentioning
confidence: 99%
“…This imaging technology can monitor enteric neuron development and turnover 72 , which can be a useful technique for analyzing disease models like Hirschsprung's disease, to monitor aganglionosis in the distal colon 73,74 . While in vitro and ex vivo experiments provide useful data regarding ENS dynamics 75,76 , it is more physiologically relevant to monitor the ENS in vivo in which extrinsic pathways are intact and the ENS can interact with immune cells, enteroendocrine cells, and others 49,[77][78][79][80] . Such in vivo data will be essential for modeling the ENS in silico 79 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms by which SNS affects the ENS is largely unknown. Recently, Smith-Edwards and Najjar et al demonstrated mouse colonic myenteric neurons respond to electrical stimulation of lumbosacral parasympathetic fibers under acute, non-survival conditions 49 . Here, we used our intravital imaging technique to visualize the myenteric plexus in Wnt1-tdTomato mice over several hours through the colonic window and to test our ability to visualize this population while minimizing motion artifact ( Supplementary Fig.…”
Section: Imaging Of Bacteria and Luminal Content In The Colon In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, ExPAN stimulation initiates myenteric neuron activity and subsequent colon contractions, but only in the presence of an intact spinal cord, confirming the presence of a sensoryparasympathetic spinal circuit regulating colonic motility. The described circuit demonstrated how visceral pain is linked to colon motility and explain why pain and dysmotility co-occur in GI disorders (65). Anyway, these results complicate further the network at the base of visceral sensitivity and might preclude the possibility of achieving a selective modulation of pain.…”
Section: Peripheral Visceral Neurotransmissionmentioning
confidence: 90%